Developmental and educational inequalities among seasonal farmworkers' children: a mixed-methods study from Türkiye - Sonmez, Emre; Ertug, Aysun; Altan, Rukiyye Yildiz; Doruk, Okan; Gulcan, Aysegul Erozyurek (Pergamon-Elsevier Science Ltd, 2026)
This study aims to examine the developmental skills and academic achievement of seasonal farmworkers' children (SFC). An explanatory sequential mixed methods design was employed. The quantitative component included 806 preschool and primary school students, while the qualitative component involved interviews with 17 SFC's teachers. Quantitative data were collected using a developmental checklist and an achievement test, whereas qualitative data were obtained through semi-structured interviews. The findings indicated that SFC demonstrated significantly lower mean scores than their peers across all developmental domains. Similarly, their academic achievement was found to be significantly lower than that of their peers. According to teachers' perspectives, the primary factors contributing to these developmental and academic disadvantages included irregular school attendance, families' limited interest in and support for their children's education, and the challenging living conditions associated with tent life.
Keywords: Seasonal Farmworker; Development Skills; Academic Achievement; Absenteeism